Pelaksanaan Pembelajaran CTL Dengan Metode Diskusi Kelompok Untuk Meningkatkan Daya Serap Siswa Pada Mata Pelajaran IPS - Hasanah, Uswatun (Alpatih Harapan Semesta, 2024)
This research was carried out at MTs. Jonggat State, Central Lombok in class VIIIb odd semester of the 2011/2012 Academic Year. This research uses Classroom Action Research (PTK), so that researchers have the opportunity to plan ideas to improve students' critical thinking skills and abilities in the teaching and learning process. In this research, researchers used classroom action research (PTK) because classroom action research is a form of strategy for detecting and solving problems through real action. Classroom action research (CAR) is trying to achieve and find a solution to problems related to the implementation of learning in the classroom.